Health care utilisation and problems in accessing health care of female undocumented immigrants in the Netherlands - Schoevers, Marianne A. (SP Birkhäuser Verlag Basel, 2010)
OBJECTIVE: To obtain information about the actual use of health care facilities by undocumented women and to identify obstacles they experience in accessing health care facilities. METHODS: A mixed methods study, with structured questionnaires and semi-structured interviews, was chosen to obtain a complete understanding. One-hundred undocumented women were recruited. Diversity was sought according to age, origin and reason for being undocumented. RESULTS: Undocumented female immigrants have unmet health care needs (56%) and low health care utilisation. Sixty-nine per cent of the women reported obstacles in accessing health care facilities. These included many personal obstacles such as shame, fear and/or lack of information. Poor language proficiency (OR 0.28;. CI 0.09–0.90) reduces utilisation of primary health care services. CONCLUSION: Health care utilisation of undocumented women is low. Undocumented women refrain from seeking health care because of personal obstacles. These women need to be identified and informed about their rights, the health care system and the duty of professional confidentiality of doctors. Finally, institutional obstacles to access care should be removed since they strengthen reluctance to seek help.